IgE to wheat, prick test, and Patch test among children with celiac disease - Marjaneh Khalighi; Hazhir Javaherizadeh; Mehran Hakimzadeh; Mitra Ahmadi; Mehdi Torabizadeh; Abbas Fayezi (BMC, 2024)
Abstract Introduction and aim Celiac disease is one of the most common autoimmune disorders. This study aimed to evaluate the relationship between celiac disease and wheat sensitization. Subjects and methods In the current study, children aged < 18 years with confirmed celiac disease were included. Data were analyzed using SPSS. Results Gastrointestinal problems were the most common indication for evaluation in terms of celiac disease. Prick and patch tests were positive in 43.4% and 34% respectively. Conclusion Prick test and patch test for wheat sensitization were positive in about 30-45% of the children for celiac disease.